(untitled) (Transport systems and technologies, 2019)
This paper presents the procedure on determination of the actual value of the specific braking force of a passenger car based on the results of train brake tests and solution of the differential motion equation when braking. The design dependences of the determination of the actual values of specific braking forces and calculated braking coefficients have been given. The results of running brake tests of a passenger car with disc brake show that the error in determination of the specific brake force does not exceed 1%. The example of the results of running brake tests of a passenger car with disc brake shows that the error in determining the specific braking force does not exceed 1%. An algorithm for determining the actual values of specific braking forces (braking efficiency) of a passenger car based on the results of running brake tests has been proposed. The described methodology is based on mathematical formulas, the coefficients of which are determined as a result of solving the differential equation of motion of the car. The technique allows to obtain additional characteristics of the braking processes and, therefore, to perform a more in-depth analysis of the braking systems of passenger cars.